2022
DOI: 10.1038/s41598-022-26347-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase-adaptive brain stimulation of striatal D1 medium spiny neurons in dopamine-depleted mice

Abstract: Brain rhythms are strongly linked with behavior, and abnormal rhythms can signify pathophysiology. For instance, the basal ganglia exhibit a wide range of low-frequency oscillations during movement, but pathological “beta” rhythms at ~ 20 Hz have been observed in Parkinson’s disease (PD) and in PD animal models. All brain rhythms have a frequency, which describes how often they oscillate, and a phase, which describes the precise time that peaks and troughs of brain rhythms occur. Although frequency has been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In closing, the current study revealed unique oscillatory signaling dynamics in the IL-NAcSh circuit during innate versus learned negative affect that differed in male and female rats. While our previous optogenetic work implicated a role of this circuit in learned negative affect only in male rats ( 31 ), future studies using other techniques such as closed-loop signal processing and optogenetics are needed to determine whether the specific oscillatory signaling properties that were observed here are indeed causally linked to innate and/or learned negative affect ( 45 , 46 , 47 , 48 , 49 ). Nevertheless, our findings clearly show that while innate and learned affective behaviors do not differ across sex, signaling dynamics in the IL-NAcSh are not engaged in the same manner in male and female rats.…”
Section: Discussionmentioning
confidence: 86%
“…In closing, the current study revealed unique oscillatory signaling dynamics in the IL-NAcSh circuit during innate versus learned negative affect that differed in male and female rats. While our previous optogenetic work implicated a role of this circuit in learned negative affect only in male rats ( 31 ), future studies using other techniques such as closed-loop signal processing and optogenetics are needed to determine whether the specific oscillatory signaling properties that were observed here are indeed causally linked to innate and/or learned negative affect ( 45 , 46 , 47 , 48 , 49 ). Nevertheless, our findings clearly show that while innate and learned affective behaviors do not differ across sex, signaling dynamics in the IL-NAcSh are not engaged in the same manner in male and female rats.…”
Section: Discussionmentioning
confidence: 86%
“…Transgenic mice have been a valuable tool for understanding the D1DR+ population in various brain circuits and areas (Lemberger et al, 2007). Previously, our group has used D1-Cre mice to modulate local cortical and striatal networks, which has the potential to improve both cognition and movement (Kim et al, 2017(Kim et al, , 2022Kim and Narayanan, 2019). Although D1DR+ neurons expressing Cre recombinase are a powerful tool, D1-Cre mice are derived from BAC-transgenic lines and thus, can have insertion position effect that can exhibit variability in transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Future stimulation approaches carefully titrated to striatal physiology may influence interval timing without affecting movement 48 .…”
Section: Discussionmentioning
confidence: 99%